A Guide Text or Many Texts? "That is the Question" - Delgado de Valencia Sonia (Universidad Nacional de Colombia, 2001)
The use of supplementary materials in the classroom has always been an essential part of the teaching and learning process. To restrict our teaching to the scope of one single textbook means to stand behind the advances of knowledge, in any area and context. Young learners appreciate any new and varied support that expands their knowledge of the world: diaries, letters, panels, free texts, magazines, short stories, poems or literary excerpts, and articles taken from Internet are materials that will allow learnersto share more and work more collaboratively. In
this article we are going to deal with some of these materials, with the criteria to select, adapt, and create them that may be of interest to the learner and that may promote reading and writing processes. Since no text can entirely satisfy the needs of students and teachers, the creativity of
both parties will be necessary to improve the quality of teaching through the adequate use and adaptation of supplementary materials.